A Two-Dimensional Framework for Psychological Research on Urban Society Analyzing Facebook Use and Subjective Well-Being - Cheng, Cecilia (Psychological Research on Urban Society, 2018)
The present research aimed to classify 155 undergraduate students’ Facebook activity using a two- dimensional framework: mode of Facebook communication and motive of Facebook use. The research also aimed to address the less explored issue of Facebook users’ appraisals in addition to their Facebook use. The results indicate that satisfaction with both private and public social communication is positively linked to positive affect, but not to negative affect. Satisfaction with private social communication explained 9% of the variance in positive affect beyond that explained by perceived peer support. The results show the efficacy of the new two-dimensional framework: the Facebook Use and Satisfaction Scale.